Stress distributions and crack growth in riveted lap joints fastening thick steel plates. (September 2018) - Kafie-Martinez, Jackeline; Keating, Peter B.; Chakra-Varthy, Pranav; Correia, José; de Jesus, Abílio
Abstract: Single shear lap joints have been a common method to fasten steel plates in railroad bridges and can be highly susceptible to fatigue cracking under the cyclic loading bridges experience. To better comprehend the fatigue process of these connections, it is important to understand the stress state near the rivet hole. While the fatigue behavior of these riveted connections has been studied, few have been carried out on stress distribution and crack formation in riveted lap joints fastening thick steel plates. This study is to provide information regarding the stress distributions developed in a single shear lap joint connecting plates of varying thicknesses. Results from the stress contour analysis are utilized to detect possible regions for fatigue crack nucleation under cyclic heavy axle loads. The study also provides information regarding the fatigue crack geometry typically found in single shear lap joints. Highlights of the work: A procedure for performing a finite element simulation of a single shear riveted lap joint is proposed. A mesh convergence study is carried out to determine the effect of element size on the accuracy of the results. Deformation behavior and stress contours near the rivet hole for the base model are shown. Longitudinal and clamping stress distributions are shown for different plate thicknesses. Thin plates are benefit by the clamping force generated during the rivet installation process, since it induces a localized compressive stress that hinders crack initiation and propagation. This beneficial effect fades away in thicker elements.